2014
DOI: 10.1097/qad.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of transmitted HIV drug resistance and HIV-exposure categories

Abstract: TDR prevalence is stabilizing in high-income countries, but increasing in low/middle-income countries. This is likely due to the low, but increasing, coverage of antiretroviral therapy in these settings. Transmission of TDR is most prevalent among MSM worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 49 publications
1
51
4
1
Order By: Relevance
“…Unfortunately, use of antiretroviral drugs in highincome countries (HICs) has also led to the emergence of HIV-1 drug resistance in many treated individuals (1). With high prevalence of HIV-1 drug resistance in the late 1990s/early 2000s, at least 10% of new infections were established by drug-resistant HIV-1 strains in HICs (4)(5)(6). In low-to middle-income countries (LMICs), poor access to clinical care, intermittent supply of antiretroviral drugs, and costs of travel to reach care providers result in suboptimal ART adherence, so that treatment failures and emergence of HIV-1 drug resistance have doubled in the last 10 years (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, use of antiretroviral drugs in highincome countries (HICs) has also led to the emergence of HIV-1 drug resistance in many treated individuals (1). With high prevalence of HIV-1 drug resistance in the late 1990s/early 2000s, at least 10% of new infections were established by drug-resistant HIV-1 strains in HICs (4)(5)(6). In low-to middle-income countries (LMICs), poor access to clinical care, intermittent supply of antiretroviral drugs, and costs of travel to reach care providers result in suboptimal ART adherence, so that treatment failures and emergence of HIV-1 drug resistance have doubled in the last 10 years (6).…”
mentioning
confidence: 99%
“…With high prevalence of HIV-1 drug resistance in the late 1990s/early 2000s, at least 10% of new infections were established by drug-resistant HIV-1 strains in HICs (4)(5)(6). In low-to middle-income countries (LMICs), poor access to clinical care, intermittent supply of antiretroviral drugs, and costs of travel to reach care providers result in suboptimal ART adherence, so that treatment failures and emergence of HIV-1 drug resistance have doubled in the last 10 years (6). With increased treatment access and high frequencies of treatment failures, HIV-1 with primary drug resistance is already found in 2% to 10% of treatment-naive individuals in Uganda, an increase of less than 1% to as high as 6.5% over the past 10 years (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Despite this decline in acquired resistance, levels of TDR have remained relatively stable over 1999-2013 although TDR rates and trends varied by geographical region, risk group and drug class [13]. An in-depth analysis demonstrated that TDR slightly increased during times lacking access to new drugs and only sharply decreased upon the introduction of a new potent drug class, such as boosted protease and integrase inhibitors, keeping the overall TDR trend stable [14].…”
Section: Changing Scenes In Antiviral Therapy and Drug Resistancementioning
confidence: 96%
“…In at least fourteen countries on the African continent, at least 80% of eligible people living with HIV were not receiving HAART at the end of 2012 (UNAIDS, 2013). Finally, and particularly in low-and middle-income countries, use of ARVs has been associated with the emergence of drug-resistant viral strains (Pham et al, 2014;Wensing et al, 2014). Thus additional therapeutic options to combat the HIV pandemic on the African continent remain urgently needed.…”
Section: Introductionmentioning
confidence: 98%